2015
DOI: 10.1111/ped.12705
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of drug‐resistant epilepsy in childhood: An Italian study

Abstract: Predictive factors of DR can be recognized in a large number of patients with epilepsy at disease onset, although the current possibility of predicting epilepsy outcome remains limited. In the long term, evidence of cerebral lesions appears to become the most significant prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…In addition, the pattern of the pathological finding of MRI was also considered a risk factor for the development of intractable epilepsy. Russo et al (23) conducted a study for this purpose and found structural and heterogeneous brain malformations more frequently. In our study, structural and congenital anomalies (34.6%) were the most common pathologies found in the intractable epilepsy group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the pattern of the pathological finding of MRI was also considered a risk factor for the development of intractable epilepsy. Russo et al (23) conducted a study for this purpose and found structural and heterogeneous brain malformations more frequently. In our study, structural and congenital anomalies (34.6%) were the most common pathologies found in the intractable epilepsy group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that the main clinical predictors of pharmacoresistance are the presence of psychiatric [82] and depressive [83,84] disorders, as well as organic brain pathology diagnosed with the MRI [85,86]. In adults, the predictors of pharmacoresistance in epilepsy include the early age of the debut, frequent seizures, failure of previous therapy, diffuse epileptiform According to some authors, an adequate choice of pharmacotherapy considering the possible drug interactions and the individual characteristics of the patient may be the way to overcome pharmacoresistance in epilepsy and concomitant diseases [88,89].…”
Section: Current Options Of Identifying Predictors Of the Antiepileptmentioning
confidence: 99%
“…Several clinical characteristics were found to be indicative of a higher risk for resistance to ASMs. Symptomatic etiology, history of perinatal insults, earlier age of onset, history of febrile seizure, presence of multiple types of seizure, complex partial seizure, abnormalities on EEG or brain imaging, and poor response to first drug have been associated with drug resistant epilepsy [4,6,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%